Novel Ta/chitosan-doped CuO nanorods for catalytic purification of industrial wastewater and antimicrobial applications. Issue 27 (7th June 2022) - Ikram, M.; Shahzadi, A.; Hayat, S.; Nabgan, W.; Ul-Hamid, A.; Haider, A.; Noor, M.; Goumri-Said, Souraya; Kanoun, Mohammed Benali; Ali, S.
Abstract : Novel tantalum (Ta) and chitosan (CS)-doped CuO nanorods (NRs) were synthesized using a single step co-precipitation route. Abstract : Novel tantalum (Ta) and chitosan (CS)-doped CuO nanorods (NRs) were synthesized using a single step co-precipitation route. Different concentrations (2 and 4%) of Ta were used in fixed amounts of CS and CuO to examine their catalytic activity and antimicrobial potential. For critical analysis, synthesized NRs were systematically examined using XRD, FTIR HRTEM, EDS, UV-Vis and PL spectroscopy. The XRD technique revealed the monoclinic structure of CuO while an increase in its crystallite size (from 15.5 to 18.5 nm) was observed upon doping. FTIR spectra were examined to study the functional groups of CuO where peaks at 514 cm −1 and 603 cm −1 confirmed the formation of CuO NRs. PL spectra depicted the charge transfer efficiency of the synthesized samples. The presence of dopants (Ta and CS) and constituent elements (Cu, O) was detected using EDS spectra. Additionally, the pH based catalytic performance of fabricated NRs revealed 99.7% dye degradation of toxic methylene blue (MB) dye in neutral media, 99.4% in basic media and 99.5% in acidic media along with promising antibacterial activities for Gram negative/positive bacteria, respectively upon doping of Ta (4%) into CS/CuO. The adsorption energies of CuO co-doped with CS/Ta led to the creation of stable structures that were investigated theoretically using density functional theory.